Flow behavior and syneresis of ball milled rice starch and their correlations with starch structure - González, Luciana C. (2021)
Fil: González, Luciana C. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Industrias; Argentina